2019
DOI: 10.1002/oby.22414
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Evaluation of the Barriers to Healthy Eating Scale: Results from Four Independent Weight Loss Studies

Abstract: Objective The purpose of this study was to evaluate the psychometric properties of the 22‐item Barriers to Healthy Eating (BHE) scale in four independent weight loss studies conducted over 13 years. Methods Principal axis factoring with promax rotation was performed to reveal the underlying factor structure. Internal consistency was assessed using Cronbach α, and convergent validity was assessed by correlating the baseline BHE with the Weight Efficacy Lifestyle questionnaire total and subscale scores. Predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…The commonality ( h 2 ) was analyzed for the 15 items. This is a measure that expresses the amount of common variance in each item that is explained by the factors; therefore, those items with low communalities (<.40) should be considered for removal given their low contribution to the final factorial solution (Sun et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The commonality ( h 2 ) was analyzed for the 15 items. This is a measure that expresses the amount of common variance in each item that is explained by the factors; therefore, those items with low communalities (<.40) should be considered for removal given their low contribution to the final factorial solution (Sun et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the interitem correlations (rho coefficients) were calculated to detect possible redundancy among items. Items with ρ > .80 were considered to be potentially redundant (Sun et al, 2019). To determine discriminant validity (if each factor should attain a different dimension from the rest), Phi-square coefficients were calculated to measure the degree of association between factors.…”
Section: Methodsmentioning
confidence: 99%
“…A highly significant X2-value for the Bartlett's test of sphericity and a Kaiser-Meyer Olkin value of 0.82 indicated that the data was suitable for calculating an EFA. All indicators revealed high communalities, with values between 0.54 and 0.89 [107,108]. Based on BMI theory reasoning, an EFA was applied, restricting the solution to seven factors.…”
Section: Definition and Validation Of The Measurement Instrumentmentioning
confidence: 99%
“…A highly significant X2-value for the Bartlett's test of sphericity and a Kaiser-Meyer Olkin value of 0.86 showed that the data was adequate for conducting an EFA. All indicators revealed high communalities, with values between 0.34 and 0.83, being the lower value close to the cut-off of 0.4, thus, items were considered to be well represented [108]. Based on theory reasoning, the EFA was conducted restricting the solution to three factors.…”
Section: Definition and Validation Of The Measurement Instrumentmentioning
confidence: 99%
“…In addition, inter-item correlations were calculated to detect possible redundancy among items (r>0.80) [27]. Construct validity was defined as the presence of substantial and significant correlations between different instruments designed to assess a common (convergent) and different (divergent) construct [28].…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%